New lensed quasars from the MUSCLES survey - Jackson, N.; Rampadarath, Hayden; Ofek, E.; Oguri, M.; Shin, M. (Wiley-Blackwell Publishing Ltd., 2012)
Gravitational lens systems containing lensed quasars are important as cosmological probes, as diagnostics of structural properties of the lensing galaxies and as tools to study the quasars themselves. The largest lensed quasar sample is the Sloan Digital Sky Survey (SDSS) Quasar Lens Search (SQLS), drawn from the SDSS. We attempt to extend this survey using observations of lens candidates selected from a combination of the quasar sample from the SDSS and the UKIRT Infrared Deep Sky Survey (UKIDSS). This adds somewhat higher image quality together with a wider range of wavelength for the selection process. In previous pilot surveys we observed five objects, finding two lenses; here we present further observations of 20 objects in which we find four lenses, of which two are independently discovered in SQLS. Following earlier work on the combination of these two surveys, we have refined our method and find that use of a colour-separation diagnostic, where we select for separations between components which appear to decrease in wavelength, is an efficient method to find lensed quasars and may be useful in ongoing and future large-scale strong lensing surveys with instruments such as Pan-STARRS and LSST. The new lenses have mostly high flux ratios, with faint secondaries buried in the lensing galaxy and typically 6–10 times less bright than the primary. Our survey brings the total number of lenses discovered in the SDSS quasar sample to 46, plus 13 lenses already known. This is likely to be up to 60–70 per cent of the total number of lensed quasars; we briefly discuss strategies by which the rest might be found.